New Ibuprofen Cystamine Salts With Improved Solubility and Anti‐Inflammatory Effect - Simay Denizkusu; Ece Sabuncu; Hande Sipahi; Prof. Duygu Avci (ChemistryOpen)
Abstract Two novel ibuprofen cystamine salts (IBU‐CYS 1 and IBU‐CYS 2) are synthesized by coupling the anion of ibuprofen with cystamine dihydrochloride in 1 : 1 and 2 : 1 ratio to improve the solubility and bioavailability of ibuprofen. The salts are characterized by 1H NMR, FT‐IR and UV‐Vis spectroscopy, differential scanning calorimetry (DSC), thermogravimetry (TGA, DTA) and X‐ray diffraction measurements. IBU‐CYS 1 and IBU‐CYS 2 show higher solubility (6.11 and 7.81 mg/mL) compared to ibuprofen (0.04 mg/mL) in water. IBU‐CYS2 was encapsulated into 2‐hydroxyethyl methacrylate: poly (ethylene glycol) acrylate hydrogels for enhanced delivery. The in vitro studies in PBS (pH 7.4) indicate that the salts are effective in relieving inflammatory responses induced by lipopolysaccharide in RAW264.7 macrophage cells (nitrite inhibition percentages of IBU‐CYS 1, IBU‐CYS 2 and ibuprofen: approximately 34.29, 27.03 and 31.50 respectively) while indicating no cytotoxicity. Therefore, these salts may be promising candidates for the development of effective formulations of this drug.